EMERGING TECHNOLOGIES FOR FOOD PROCESS - Assawarachan, Rittichai (Life Sciences and Environment Journal, 2017)
Emerging technologies for food processing is consisted of the improvement of thermal and non-thermal processing. Novel thermal technology using the ohmic heating (OH) and the dielectric heating, such as microwave (MW) and radio frequency heating (RF). These heating systems have been applied to increase the efficiency of the conventional thermal processing at a high temperature for a short time (HTST) and the drying processing. In contrast, non-thermal processing using pulsed electric field (PEF) and high pressure processing (HPP) is the innovation for low temperature applications in food which keeps the sensorial and nutritional properties of the food close to fresh products and maintains its original freshness throughout the shelf-life because of the absence of heat treatment. The purpose of this article was to systematically review the related literatures in accordance with the recent researches as a guideline for research and development of emerging technologies for food processing.